Fetal absent/hypoplastic nasal bone: a single center follow up study from a tertiary referral hospital in India - Prasad, Cini Sudhakar; Kunjukutty, Radhamony; Krishnan, Vivek (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: This study was undertaken to determine perinatal outcomes in fetuses with absent/hypoplastic nasal bone (AHNB) when considered as a broad entity irrespective of time at which it is identified and identify subgroups with the highest risk of abnormal outcome based on screening status and associated findings. Methods: This was an observational study involving a total of 142 pregnant women whose fetuses were identified with AHNB by ultrasongraphy (USG) during a three year period from January 2016 to December 2018. These women were offered aneuploidy screening/non-invasive prenatal testing (NIPT) or direct invasive testing either alone or in combination. Outcome data was collected and a sub-group analysis was done by dividing them into 8 subgroups based on screening status and associated findings. Results: Out of 12758 scans done during the study period, 142 fetuses (1.11%) were identified with AHNB. 80 (56%) opted the biochemical screening test, 5 (3.5%) opted NIPT while 60 (42.9%) opted for invasive testing. 21 (14.8%) had an abnormal karyotype. In sub-group analysis, the best outcome was seen in group 1, where the biochemical screening was negative and no other aneuploidy markers or anomalies were seen. Conclusions: The present study confirms the association of AHNB with chromosomal disease. However, isolated AHNB with low risk in biochemical screening is rarely associated with aneuploidy. In contrast, a significant no of fetuses yielded abnormal chromosome results when AHNB was associated with high risk in biochemical screening, additional aneuploidy markers or associated anomalies.